A comparative study of two microscopic road traffic simulators - Ng, Zi Peng (2018)
In many urban areas, the daily lives of people revolve around traveling a long distance from one destination to another. To support such mobility many urban areas in the different country employed an extensive use of private and public transport that runs on a road network. In Singapore, it had shown a steady increase of motor vehicle from 851,336 in 2007 to 961,842 in 2017. Therefore, any changes to the road network will have a significant impact on the society. Thus, any future implementation of the road network will have to be first simulated using a multi-agent system to study the what-if scenario before deciding if the project should be implemented. The aim of this project is to make a comparative study between different state-of-the-art traffic simulators that have a different specification to see if they could simulate similar result. It will also highlight the finding of what could have been changed to the focus simulator, CityMoS to reduce the margin of error. One of the main tasks of the project is to configure the experimental setup to replicate a commercial state-of-the-art traffic simulator, VISSIM such that an accurate study could be conducted. Hence, calibration and validation using various mathematics model will be used in the project. Furthermore, parameter chosen to be calibrated to evaluate the result will be those that have a significant impact on the travel time of the simulated agents. The project had been completed successfully to a certain extent in which the calibration of parameter had a result of as close as 2.5% normalize root mean square error rate. In addition, several factors that cause the inaccuracy was found during the runs of the simulation. Finally, recommendation on how to improve the simulator to reduce the margin of error was also given for future implementation.